Information on the genetic diversity of Theileria parva populations in cattle and buffalo in Tanzania - CGIAR Research Program on Livestock (2021)
This is a first report on the genetic diversity of Theileria parva populations in cattle and buffalo in an area where livestock co-exist with buffalo (T. parva is the causative agent of East Coast Fever, a devastating cattle disease).